Calidad microbiológica y caracterización fisicoquímica y espectrométrica del óleo de Iguana iguana (iguana) de uso etnomedicinal, Iquitos 2024 - Murcia Hidalgo, Susan Beatriz (2025)
The present study aimed to analyze the microbiological quality and characterize the physicochemical and spectral properties of Iguana iguana oil, traditionally used for therapeutic purposes in the city of Iquitos, Peru. This was a descriptive, non experimental, cross-sectional, and prospective study. Five oil samples were collected from “Pasaje Paquito,” a market known for the sale of ethnomedicinal products. Microbiological analyses were carried out in accordance with USP 40 tests 61 and 62 to determine the presence of mesophilic bacteria and specific pathogens. In addition, physicochemical parameters were evaluated, including density, acid value, iodine value, peroxide value, and saponification index. a chromatographic analysis using mass spectrometry was also performed to identify the fatty acid profile. The results showed that I. iguana oil contains 44.82% monounsaturated fatty acids and 43.19% saturated fatty acids, with oleic acid (34.9%) and palmitic acid (28.9%) being the most prevalent. Essential fatty acids such as linoleic and linolenic acids were also identified, which are associated with anti-inflammatory and regenerative properties. However, the stability of the product was compromised due to its high acid value (2.52) and peroxide value (62.75 meq o₂/kg), as well as poor microbiological quality: two samples were contaminated with E. coli, failing to meet established safety standards. This study contributes to the recognition of ancestral knowledge in the amazon region and provides scientific evidence on a widely used traditional product, laying the groundwork for future research into its therapeutic potential.